Stimulation, segregation and scandal: geographies of prostitution regulation in British India, between Registration (1888) and Suppression (1923) - Legg, Stephen (Cambridge University Press, 2012)
This paper explores the regulation of prostitution in colonial India between the abolition of the Indian Contagious Diseases Act in 1888 and the passing of the first Suppression of Immoral Traffic Act in 1923. It challenges the commonly held assumption that prostitutes naturally segregated themselves in Indian cities, and shows that this was a policy advocated by the Government of India. The object was to prevent the military visiting these segregated areas, in the absence of effective Cantonment Regulations for registering, inspecting, and treating prostitutes. The central government stimulated provincial segregation through expressing its desires via demi-official memoranda and confidential correspondence, to which Rangoon and Bombay responded most willingly. The second half of the paper explores the conditions, in both India and Ceylon, that made these segregated areas into scandalous sites in the early twentieth century. It situates the brothel amongst changing beliefs that they: increased rather than decreased incidents of homosexuality; stimulated trafficking in women and children; and encouraged the spread of scandalous white prostitutes ‘up-country’, beyond their tolerated location in coastal cosmopolitan ports. Taken alongside demands that the state support social reform in the early twentieth century, segregation provided the tipping point for the shift towards suppression from 1917 onwards. It also illustrates the scalar shifts in which central-local relations, and relations between provinces, in government were being negotiated in advance of the dyarchy system formalized in 1919.